Students’ Social Initiatives as A Prerequisite for Sustainable Development of Social Entrepreneurship: A Case Study in Bulgaria - Kyurova, Vyara; Koyundzhiyska-Davidkova, Blagovesta (European Journal of Sustainable Development, 2023)
Social entrepreneurship is an important source of economic growth and a driver of the social economy. An important condition for its development and the creation of a business in this sphere is the participation of the individual in social initiatives. Summarizing the scientific ideas shows that the issue of social entrepreneurship is relatively well understood, while that of social initiatives is very poorly addressed. Considering this fact, the authors seek to obtain more information regarding the essence of social initiatives and the readiness of students to participate in its. The aim of the present study is to determine the desire and opportunities among students for their involvement in social initiatives and their attitudes towards starting a social entrepreneurial business. To achieve the goal, students from Bulgarian higher education institutions were surveyed using the respondent method. The application of this method is appropriate because of its adequacy in terms of the specificity of both the subjects studied and the data to be obtained. The survey used in the study contains close-ended questions aimed at ascertaining students' participation in social initiatives, as well as their views on starting a social entrepreneurial business. The findings of the study show that there are certain problems related to the organization of social initiatives and in terms of starting a social entrepreneurial business. A significant result of the study is that the enabling environment for the development of social entrepreneurship significantly influences the possibility of creating student social initiatives at the university. The study can be used as a model for analysis of the relationship between social entrepreneurship and students’ social initiatives. Keywords: social entrepreneurship, social initiatives, students, Bulgaria